(untitled) (Journal of Parents and Teachers, 2014)
We only talk about the collapse of the Prestige and the negative consequences for the environment that this entails. However, in the face of this catastrophic situation that should never have happened, more than 20,000 volunteers of different ages and nationalities have come out to help. Thanks to them 30,000 tons of fuel have been collected and it is that, despite the tragedy of the black tide, the white tide has given us a lesson of solidarity that we will not forget.